Temporal stability of morph frequency in central European populations of Adalia bipunctata and A. decempunctata (Coleoptera: Coccinellidae) - Alois HONĚK; Zdeňka MARTINKOVÁ; Stano PEKÁR (European Journal of Entomology, 2005)
In central Europe Adalia bipunctata (L.) occurs in two main colour morphs (typical, melanic), and A. decempunctata (L.) occurs in 3 morphs (spotted, chequered, dark). Temporal variation in the relative frequency of morphs was recorded in populations of the Czech Republic where geographic variation in morph frequency is low. Seasonal trends were investigated in samples collected by a light-trap run daily from March to November for 14 years. In A. bipunctata the melanic form was more abundant in autumn than in spring but the difference was not significant. In A. decempunctata morph proportions did not change seasonally. Samples were also collected by sweepnet from stands of many plant species. In both Adalia species the morph proportions did not differ significantly among collections made on different plants. Long-term changes in morph proportions were analysed by pooling annual samples over all host plants. In A. bipunctata, sampled in 15 years between 1971-2004, there was no significant change in proportion of typical (90.1%) and melanic (9.9%) forms. In A. decempunctata, sampled in 12 years between 1976-2004, the proportions of "spotted" (mean over the years 29.4%), "chequered" (42.2%) and "dark" (21.3%) morphs varied between years. There was a trend toward an increasing proportion of the spotted form in the 2000s compared to the 1970s and 1980s.